Measures to Enhance the Applications of Eco Labels in Malaysian Construction Industry - Zawana, Yong Iffah; Ismail, Zulhabri (International Journal of Sustainable Construction Engineering and Technology, 2015)
As Malaysia is forecasted to be confronted with energy scarcity and variety of resource consumption for growing population and development, green urban planning and practices of energy use and consumption are the keys components for sustainable future. Hence, in the context of sustainable development, Malaysia’s construction industry is now calling for green practices and procurement in their industry. The international community had adopted measures to reduce environmental damage by establishing eco labelling schemes and also promoting the sustainable design and concepts. It started with the Malaysian government also has responded very positively to this matter. In 1996, Standards and Industrial Research Institute of Malaysia (SIRIM) launched the national eco-labelling program verifying products according to environmental criteria as tools and initiatives to express concern and support to sustainable development. Taking into consideration the infancy stage of the Malaysia green marketing initiative, this study therefore conducted with the aim to propose measures to enhance the applications of Eco Labels in Malaysian construction industry.  The objectives of the research are to investigate the existing policies pertaining the eco labelling, to determine the factors in implementing the eco labelling scheme as well as to identify the barriers and possible measures to further enhance the use of eco labelling in construction industry. Survey were conducted via variables from the literature review regarding the policies pertaining the eco labelling in Malaysia and questionnaire method for factors and barriers to implement the eco labels and the measures to enhance the application of eco labels with respondents from various construction companies among construction players that have involved and experienced with green project.  Data obtained were analysed using Average Index and Correlation method via the SPSS.  The result shown that, the applications of eco labels product among construction players were relatively acceptable which still can be utilised with most of the significant measures to be proposed.